2019
DOI: 10.1002/jmri.26725
|View full text |Cite
|
Sign up to set email alerts
|

Total cerebrovascular blood flow and whole brain perfusion in children sedated using propofol with or without ketamine at induction: An investigation with 2D‐Cine PC and ASL

Abstract: Background Multiple sedation regimes may be used to facilitate pediatric MRI scans. These regimes might affect cerebral blood flow and hemodynamics to varying degrees, particularly in children who may be vulnerable to anesthetic side effects. Purpose To compare the effects of propofol monosedation solely (Pm group) vs. a combination of propofol and ketamine (KP group) on brain hemodynamics and perfusion. Study Type Prospective double‐blind randomized trial. Field Strength/Sequences 1.5T and 3T. 2D‐Cine phase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…At the insertion point of bronchoscopy, the elevated level of MAP and HR in remifentanil were signi cantly higher than that in esketamine group, indicating that esketamine provided better circulative stability. Similar to this study, Hegazy MA reported that the combination of fentanyl and propofol inhibited hemodynamics [21], but the combination of ketamine and propofol led to stable hemodynamics [22]. However, neither remifentanil combination nor esketamine combination completely prevented the increase in blood pressure and heart rate caused by endotracheal intubation, but such increase in blood pressure and heart rate was well tolerated and did not require any intervention.…”
Section: Discussionsupporting
confidence: 70%
“…At the insertion point of bronchoscopy, the elevated level of MAP and HR in remifentanil were signi cantly higher than that in esketamine group, indicating that esketamine provided better circulative stability. Similar to this study, Hegazy MA reported that the combination of fentanyl and propofol inhibited hemodynamics [21], but the combination of ketamine and propofol led to stable hemodynamics [22]. However, neither remifentanil combination nor esketamine combination completely prevented the increase in blood pressure and heart rate caused by endotracheal intubation, but such increase in blood pressure and heart rate was well tolerated and did not require any intervention.…”
Section: Discussionsupporting
confidence: 70%
“…It is important to consider that between birth and adulthood, many physiological parameters that may affect CBF measurements will evolve and can also be influenced by disease or sedation 129 (Table S2). Additionally, some sedatives and anesthetics can reduce CBF (e.g., propofol), whereas others increase CBF (ketamine without benzodiazepine) or have a variable influence on CBF depending on concentration (many narcotic gases) 130 . Consideration of all of these factors must be used when interpreting pediatric ASL imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some sedatives and anesthetics can reduce CBF (e.g., propofol), whereas others increase CBF (ketamine without benzodiazepine) or have a variable influence on CBF depending on concentration (many narcotic gases). 130 Consideration of all of these factors must be used when interpreting pediatric ASL imaging.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by two reasons: (1) The accuracy of the selected ASL technique (PCASL) is sensitive to the flow velocity of the arterial blood, and the scanning parameters were not optimized for the current cohort. Several studies have reported that the flow velocity of the arterial blood of participants was higher than those in healthy adults, and the resulting CBF can be underestimated by 8% without a correct measurement of the flow velocity (Gevers et al, 2012; Makki et al, 2019). A possible solution to improve the accuracy of CBF quantification would be to use a pulsed ASL labeling technique, which is insensitive to flow velocity variations, though this would also reduce the signal‐to‐noise ratio of the ASL data.…”
Section: Discussionmentioning
confidence: 99%